2020
DOI: 10.1017/s1355617720001009
|View full text |Cite
|
Sign up to set email alerts
|

Worth the Wait: Delayed Recall after 1 Week Predicts Cognitive and Medial Temporal Lobe Trajectories in Older Adults

Abstract: Objective: We evaluated whether memory recall following an extended (1 week) delay predicts cognitive and brain structural trajectories in older adults. Method: Clinically normal older adults (52–92 years old) were followed longitudinally for up to 8 years after completing a memory paradigm at baseline [Story Recall Test (SRT)] that assessed delayed recall at 30 min and 1 week. Subsets of the cohort underwent neuroimaging (N = 134, mean age = 75) and neuropsychological testing (N = 178–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The XGBoost classifier performed well in predicting AD risk, selecting three features (i.e., Everyday Cognition Questionnaire (Study partner) -Total, Alzheimers Disease Assessment Scale (13 items) and Delayed Total Recall) with AUC ROC values consistently above 97% (Figure 1, surpassing the performance of the latest AD-specific model (Rye et al 2022). Our findings support the idea that memory paradigms, such as delayed total recall, can serve as effective measures to track neurodegenerative disease trajectories (Lindbergh et al 2021). Moreover, these features may be sensitive to neurodegenerative disease trajectories more so than Mini-Mental State Examination or Montreal Cognitive Assessment.…”
Section: Discussionsupporting
confidence: 74%
“…The XGBoost classifier performed well in predicting AD risk, selecting three features (i.e., Everyday Cognition Questionnaire (Study partner) -Total, Alzheimers Disease Assessment Scale (13 items) and Delayed Total Recall) with AUC ROC values consistently above 97% (Figure 1, surpassing the performance of the latest AD-specific model (Rye et al 2022). Our findings support the idea that memory paradigms, such as delayed total recall, can serve as effective measures to track neurodegenerative disease trajectories (Lindbergh et al 2021). Moreover, these features may be sensitive to neurodegenerative disease trajectories more so than Mini-Mental State Examination or Montreal Cognitive Assessment.…”
Section: Discussionsupporting
confidence: 74%
“…Third, the UK Biobank cognitive test battery was not comprehensive and omitted measures that may be sensitive to early cognitive changes in AD, such as tests of episodic memory that capture long-delay recall and recognition, 63 , 64 and measures of verbal fluency, 23 language, 65 , 66 and working memory 67 or other approaches. 68 With more sensitive measures, we may have detected even earlier changes. Fourth, caution in interpreting test differences is merited because the samples differed in size and composition.…”
Section: Discussionmentioning
confidence: 97%
“…Second, we restricted analysis to individuals with European ancestry—the predominant population of previous AD-GRS studies—and our results may not reflect patterns in other populations. Third, the UK Biobank cognitive test battery was not comprehensive and omitted measures that may be sensitive to early cognitive changes in AD, such as tests of episodic memory that capture long-delay recall and recognition, and measures of verbal fluency, language, and working memory or other approaches . With more sensitive measures, we may have detected even earlier changes.…”
Section: Discussionmentioning
confidence: 99%
“…They emphasize the importance of avoiding floor and ceiling effects which may arise due to the long delays employed and variability across individuals in premorbid IQ, learning strategies, motivation and habituation to test situations. Moreover, in order to avoid rehearsal, it is desirable not to inform subjects that they will be asked again after some time about the newly learned information (C. Butler et al, 2009;Lindbergh et al, 2021;Weston et al, 2018;Zimmermann & Butler, 2018). For the first time, Alviarez-Schulze et al ( 2022) have shown evidence on the relevance of warning or not warning subjects of long-term reassessment of newly learned information by revealing that subjects who were informed of a future assessment after 1 week showed less long-term forgetting.…”
Section: Clinical Considerationsmentioning
confidence: 99%